Enhancing ESP Students’ Speaking Ability through PowerPoint-Assisted Oral Presentations (IJORER : International Journal of Recent Educational Research, 2026)
Objective:The integration of technology in English language teaching, particularly in English for Specific Purposes (ESP), has transformed classroom practices in higher education. However, students often face difficulties in speaking English fluently within their specialized subjects. This study aims to evaluate the effectiveness of PowerPoint (PPT) as a medium to enhance students’ speaking skills through oral presentations, with a focus on ESP for Business Law, an area that has received limited empirical attention. Method : This research used qualitative approach. Data were collected via observations, questionnaires, and documentation from 48 students enrolled in an English for Business Law course. Results: Findings revealed that (1) PPT effectively supports students in improving their oral communication skills, and (2) students’ speaking performance increased after conducting group presentations using PPT. Novelty: The study’s contribution lies in demonstrating how structured PPT-based presentations can enhance subject-specific oral proficiency in ESP classrooms. These results suggest that lecturers and students should consider integrating PPT in oral presentations to promote language development and engagement in higher education settings.